Spasticity in adults with cerebral palsy and multiple sclerosis measured by objective clinically applicable technique. Issue 9 (September 2018) - Yamaguchi, Tomofumi; Hvass Petersen, Tue; Kirk, Henrik; Forman, Christian; Svane, Christian; Kofoed-Hansen, Mathilde; Boesen, Finn; Lorentzen, Jakob
Highlights: A clinically applicable method provides valid and reproducible measurement of ankle stiffness. Increased stiffness in the triceps surae muscle tendon complex was found in cerebral palsy (CP) and multiple sclerosis (MS) subjects. CP and MS had reduced range of movement in the ankle joint compared to healthy subjects. Abstract: Objective: The present study evaluated ankle stiffness in adults with and without neurological disorders and investigated the accuracy and reproducibility of a clinically applicable method using a dynamometer. Methods: Measurements were obtained from 8 healthy subjects (age 39.3), 9 subjects with spastic cerebral palsy (CP) (age 39.8) and 8 subjects with multiple sclerosis (MS) (age 49.9). Slow and fast dorsiflexion stretches of the ankle joint were performed to evaluate passive muscle-tendon-joint stiffness, reflex mediated stiffness and range of movement (ROM), respectively. Intra/inter-rater reliability for passive and reflex mediated ankle muscle stiffness was assessed for all groups. Results: Subjects with CP and MS showed significantly larger values of passive stiffness in the triceps surae muscle tendon complex and smaller ROM compared to healthy individuals, while no significant difference in reflex mediated stiffness. Measurements of passive muscle-tendon-joint stiffness and reflex mediated stiffness showed good to excellent inter- and intra-rater reliability (ICC: 0.62–0.91) in all groups. Conclusion: Increased stiffness was found in subjects with CP and MS with a clinically applicable method that provides valid and reproducible measurement of passive ankle muscle-tendon-joint stiffness and reflex mediated stiffness. Significance: The present technique may provide important supplementary information for the clinician.